Medical Humanitarianism of Turkey's NGOS: A "Turkish Way?". (November 2017) - Aras, Bülent
This article investigates to what extent Turkish humanitarian nongovernmental organizations (NGOs) are able to alleviate human suffering as the ultimate goal of medical humanitarianism. To answer this question, the study investigates the efficiency of Turkish humanitarian NGOs in general with a specific focus on Uganda. It explores how their aid surfaces on the ground, to what extent it is aligned with country needs and priorities, the extent to which these initiatives help to strengthen or improve existing health systems, Turkish NGOs' criteria for aid, and the challenges they face. Turkish NGOs' distribution of medical aid is aligned with country needs and priorities, and their initiatives help strengthen and improve existing health systems. However, their sustainability is threatened by challenges of overreliance on voluntarism and lack of sufficient expertise, capacity, and funding.